Global basal cell carcinoma in 55+ population: 1990– 2021 burden、risk-factor trends and 2050 forecast - Cai, Yan-Xia; Rong, Minglei (Frontiers in Oncology, 2025)
ObjectiveThis study map the 1990–2021 basal-cell carcinoma burden in people ≥55 years worldwide, pinpoint key risk drivers, and offer concise intervention guidance for elder-focused prevention.MethodsWe focused on adults aged ≥55 years because this group shows the highest basal-cell carcinoma (BCC) frequency and matches the Global Burden of Disease (GBD) age strata. Incidence and disability-adjusted life-year (DALY) counts for 1990–2021 were downloaded from the Global Health Data Exchange. After direct age-standardisation, we plotted global, regional and national rates, generated world maps, computed annual percent change (APC) and contrasted 1990 versus 2021 distributions—all with R 4.2.1. A Bayesian hierarchical model then projected the 2050 burden.Results1990-2021, Among adults ≥55 years, global basal-cell carcinoma incidence rose and then plateaued, while DALYs climbed before edging downward. The steepest gains in both age-standardized incidence and DALY rates occurred in high-income North America. Men consistently outpaced women across all metrics. The USA, Brazil and China recorded the largest absolute caseloads, yet the USA always posted the highest incidence rate and Nepal the lowest. Overall, the BCC burden has expanded over the past three decades.ConclusionOver the last three decades, both new cases and the overall toll of basal-cell carcinoma among older adults have risen worldwide, fueled by expanding and aging populations, greater ultraviolet exposure, and better case detection. Looking forward, vigorous sun-protection education and unified UV-shielding measures are essential to curb incidence and ease the growing burden.